Formulation and evaluation of the vascular endothelial growth factor loaded polycaprolactone nanoparticles - Oya Kerimoğlu; Setenay Özer-Önder; Emine Alarçin; Seher Karsli (Universidade de São Paulo, 2022)
Abstract In an attempt to increase molecular stability and provide controlled release, vascular endothelial growth factor (VEGF) was encapsulated into polycaprolactone (PCL) nanoparticles. Both VEGF-free and VEGF-loaded PCL nanoparticles were formulated by w/o/w double emulsion of the dichloromethane-water system in the presence of polyvinyl alcohol (PVA) and rat serum albumin. To achieve the optimal formulation concerning particle size and monodispersity, studies were carried out with different formulation parameters, including PVA concentration, homogenization time and rate. Scanning electron microscopy and dynamic light scattering analysis showed respectively that particles had a spherical shape with a smooth surface and particle size varying between 58.68-751.9 nm. All of the formulations were negatively charged according to zeta potential analysis. In vitro release study was performed in pH 7.4 phosphate-buffered saline at 37°C and released VEGF amount was measured by enzyme-linked immunosorbent assay (ELISA) method. At the end of the 35th day, 10% of total encapsulated VEGF was released with a sustained-release profile, which fitted the Korsmeyer-Peppas kinetic model. The bioactivation of the nanoparticles was evaluated using XTT and ELISA methods. As a result, the released VEGF was biologically active and also VEGF loaded PCL nanoparticles enhanced proliferation of the human umbilical vein endothelial cells in cell culture.